N-ethyl-n-nitrosourea induced leukaemia in a mouse model through upregulation of vascular endothelial growth factor and evading apoptosis - Abdullahi, Aliyu; Shaari, Mohd Rosly; Ahmad Sayuti, Nurul Syahirah; Reduan, Mohd Farhan Hanif; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin; Shaari, Khozirah; Hamzah, Hazilawati (MDPI, 2020)
Chemical carcinogens are commonly used to investigate the biology and prognoses of various cancers. This study investigated the mechanism of leukaemogenic effects of n-ethyl-n-nitrosourea (ENU) in a mouse model. A total of 14 3-week-old male Institute of Cancer Research (ICR)-mice were used for the study. The mice were divided into groups A and B with seven mice each. Group A served as the control while group B received intraperitoneal (IP) injections of 80 mg/kg ENU twice with a one-week interval and were monitored monthly for 3 months for the development of leukaemia via blood smear examination. The mice were sacrificed humanely using a CO2 chamber. Blood, spleen, lymph nodes, liver, kidney and lung samples were collected for blood smear examination and histopathological evaluation. The expression of angiogenic protein (VEGF), and pro and anti-apoptotic proteins (BCL2 and BAX), was detected and quantified using Western blot technique. Leukaemia was confirmed by the presence of numerous blast cells in the peripheral blood smear in group B. Similarly, the VEGF and BCL2 proteins were significantly (p < 0.05) upregulated in group B compared to A. It is concluded that IP administration of 80 mg/kg ENU induced leukaemia in ICR-mice 12 weeks post administration through upregulation of angiogenic and anti-apoptotic proteins: VEGF and BCL2.